The Lactation Management Health Education for Pregnant Women: Pendidikan Kesehatan Manajemen Laktasi Pada Ibu Hamil - Mariani; Yulia Rachmawati hasanah (CV. Multi Kreasi Media, 2022)
In breastfeeding, it is necessary to make lactation management efforts by the mother to support the success of breastfeeding, because in essence lactation management starts during pregnancy, after delivery, and during the period of breastfeeding the baby. Guided by the achievement of exclusive breastfeeding in the Probolinggo district, which is still low, so that breastfeeding education is still very much needed by young mothers. The purpose of this community partnership program is to increase understanding of mothers, especially pregnant women, who will prepare breastfeeding for their babies at birth. The method used was health education using 2 partners, namely Posyandu Jambu hamlet and Posyandu Dusun Manggis. The indicator of the success of the community partnership program is the understanding of pregnant women about lactation management in pregnant women, thereby increasing the coverage of exclusive breastfeeding. The result of this community service is that initially pregnant women plan to give their babies formula milk if the milk does not come out and does not go smoothly after receiving health education in the form of health education about lactation management in pregnant women, so they are very enthusiastic and determined to give their babies exclusive breastfeeding until age 6 months and continued with complementary breastfeeding but breastfeeding continues until the child is 2 years old.